SEAMLESS TUBE FORMING SIMULATION: COLD PILGERING AND TUBE DRAWING ANALYSIS - Bunte, Claudio; Borda, Brian (Instituto Argentino de Siderurgia, 2021)
- Simulate the tube forming by the application of Simufact forming software The simulated processes were: - cold pilgering - cold drawing - Determine conditions in order to avoid defects
Keywords: Simulation, software, tube drawing, cold drawing